Optimalisasi Hak Kekayaan Intelektual sebagai Harta Pailit - Nirmala, Mustika Suri; Wiguna, Jeniffer Natasha; Saputra, Rizky Robbi (UNES Law Review, 2023)
Bankruptcy is a condition where the debtor is unable to make payments on debts from creditors as obligations that should be fulfilled by him. The situation of inability to pay is generally caused by none other than the financial distress of the debtor's business that has regressed, which is then realized as bankruptcy through a court decision that results in a general confiscation of all assets of the bankrupt debtor, both wealth that at that time exists and wealth that will exist in the future. In the business world, there is one wealth that becomes an asset in the business world called Intellectual Property Rights (IPR). IPR is a right derived from the work, charity, and inventiveness of human intellectual abilities that have benefits and are useful in supporting human life and have economic value. So that the output of IPR as a benefit for its holders is that it can be commercialized and invite profits. However, in the legal framework in Indonesia, there is no normative arrangement that regulates the relationship between IPR as bankruptcy assets. So in this paper, the author tries to examine the relationship between the two using normative juridical research methods and using legislative approaches and conceptual approaches. As a result, by looking at various provisions related to assets, it can be concluded that IPR needs to be optimized as an asset in bankruptcy assets.